#TITLE_ALTERNATIVE# - SANDY PERDANA PANJAITAN (NIM 13003051), JAMES
Textile industry produces wastewater that requires specific treatment because of its color composition. The dyes should be removed before the waste water can be released to the environment. Recent researches showed that the wastes can be effectively treated by using white rot fungi in a modified packed bed bioreactor. The objective of this research is to evaluate the performance of the culture used in degrading indigo in the modified packed bed bioreactor. From the results of this research, potency of the system can be learnt. The method used in this research is to take primary data in a laboratory-scale research. The research variables were the immersion time of the culture (15 and 30 minutes) and the dyes used (indigo carmine and indigo bromine). For sample analysis, the absorbance of sample, protein concentration, and laccase activity were examined. The system applied Indonesian fungus, Marasmius sp., immobilized in luffa. The synthetic dyes of 100 ppm were used to evaluate the decolorization system. Results show that significant decolorization occurs in the fourth day of treatment. The absorbance (for maximum wavelength of 661 nm) decreased from about 1.556 A to 0.701 A. Laccase assay showed that a highest activity of 44.17 U/L for the treatment of indigo carmine and 14.71 U/L for the treatment of indigo bromine. The highest total protein concentration detected was 30 mg/ml. Overall, this research shows a promising potency for the treatment of textile waste water in a modified packed bed bioreactor using Marasmius sp.